“I WAS TERRIFIED OF BEING LABELLED”: SOCIAL EXPERIENCES OF EX-DROPOUTS RE-ENROLLED IN SECONDARY SCHOOL IN SOUTH AFRICA - Brown, Byron A (European Scientific Journal, ESJ, 2013)
Using qualitative methods, involving interviews, the study explored, among a sample of 10 ex-dropouts who re-enrolled in secondary schools in South Africa, whether social labels were used to define their social life and the form these social labels take, as they reintegrate at school. It also explored the reactions of these ex-dropouts to the social labels. Evidence in the literature on the effects of negative social labelling on children and adolescents, prompted the empirical investigation at schools in the Eastern Cape, South Africa. The research found that negative social labelling and teasing were persistent force in the lives of ex-dropout at school. Consistent with social labelling theory proposed by Link and colleagues, these experiences were sources of social stress for ex-dropouts. The dominant form of social labels was negative labels. This suggests that ex-dropouts continue to suffer in one form or another beyond the initial circumstances that pushed them out of school. The paper argues that as a consequence of the above evidence, the larger development potential, which the return of ex-dropout to school might offer, will remain unfulfilled unless there is a transformed school context that supports ex-dropout. Suggestions to build a supportive social environment for ex-dropouts at school have been discussed.